60. The World-Wide Inaccessible Web, Part 1: Browsing - Baggaley, Jon; Batpurev, Batchuluun (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
Two studies are reported, comparing the browser loading times of webpages created using common Web development techniques. The loading speeds were estimated in 12 Asian countries by members of the PANdora network, funded by the International Development Research Centre (IDRC) to conduct collaborative research in the development of effective distance education (DE) practices. An online survey tool with stopwatch-type counter was used. Responses were obtained from Bhutan, Cambodia, India, Indonesia, Laos, Mongolia, the Philippines, Sri Lanka, Pakistan, Singapore, Thailand, and Vietnam. In most of the survey conditions, browser loading times were noted up to four times slower than commonly prescribed as acceptable. Failure of pages to load at all was frequent. The speediest loading times were observed when the online material was hosted locally, and was created either in the Docebo learning management system (LMS), or in the HTML option provided by the Moodle LMS. It is recommended that formative evaluation of this type should become standard practice in the selection and use of online programming techniques, in order to preserve the accessibility of the World-Wide-Web across large geographical distances, as for DE in the developing world.